Ferdinand De Saussure's Semiotic Study of the Poetry “Paman Doblang” by W.S. Renda - Vita Dwi Agustin (Pedagogy Review, 2023)
Abstract: The poem "Uncle Doblang" by W.S. Rendra is a literary work that has its own charm. Apart from being a medium of entertainment, this poem also holds various meanings and intentions in it, which are conveyed by the author through the form of semiotic signs that must be understood by the reader so that the meaning can be conveyed properly. On the other hand, not everything can be given meaning without reason. The existence of semiotic studies, especially Ferdinand De Saussure's semiotics, can certainly be applied as a theory to dissect poetry from an easy level. The use of semiotic studies is to analyze the signifier and signified contained in the poetry text. This study utilizes a qualitative data analysis method, namely reducing data, then producing a conclusion. The results obtained show that the poem does contain a lot of signifiers and signifieds that describe the twists and turns of the life of a prisoner who has to spend a lot of time in a dark prison room.  Keywords: semiotic analysis, uncle doblang poem, Ferdinand de Saussure semiotics